HUBUNGAN KECERDASAN EMOSIONAL DENGAN KECEMASAN PASIEN MENJALANI HEMODIALISA - Sri Handayani, Novi Sefia Tifani; Tifani, Novi Sefia; Prihanti, Dyah Restuning (Citra Internasional Institute, 2025)
Patients undergoing Hemodialysis can experience psychological effects in the form of anxiety. Anxiety in Hemodialysis patients is caused by several factors, namely adhering to a strict diet, limiting drinking and having to witness the incident when an AV-Shunt is installed during the hemodialysis therapy carried out on their body. Management of anxiety experienced by patients is by controlling anxiety, the ability to control and control emotions, for example emotional intelligence. The aim of this study was to find out patients who experienced anxiety while undergoing hemodialysis. This type of research uses a quantitative approach with a correlational design. The sample used was patients undergoing hemodialysis using a cross sectional design with purposive sampling technique, obtaining 31 patients. The instruments in this research have been tested for validity and reliability. The bivariate test used was the Spearman rank correlation test. Based on the research results, it was found that the majority of patients at Dr. H. Soewondo Kendal had mild anxiety as many as 24 patients (77.2%), the majority of patients had very high emotional intelligence as many as 24 patients (77.4%), with a p-value of 0.002 or <0.05, and rho - 0.0.538 then shows that the correlation is strong, while the correlation direction is positive. The higher the patient's level of emotional intelligence, the lower the level of anxiety they experience.